Myocardial Infarction With Non-obstructive Coronary Arteries: Risk Factors and Associated Comorbidities - Merlo, Andrea Carlo; Troccolo, Alessandro; Piredda, Elisa; Porto, Italo; Gil Ad, Vered (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction with non-obstructive coronary arteries (MINOCA), despite a lower burden of coronary atherosclerosis, has a non-negligible prognostic impact. The label of MINOCA includes an array of different aetiologies and pathologic conditions, thus the identification of the underlying disease is crucial to patient management. Myocardial infarction (MI) with obstructive coronary artery disease and MINOCA share only some risk factors and comorbid conditions. While traditional cardiovascular risk factors have a lower prevalence in MINOCA patients, atypical ones – e.g. anxiety, depression, and autoimmune diseases – are much more frequent in this population. Other conditions – e.g. pregnancy, cancer, and anti-cancer therapy – can predispose to or even induce MINOCA through various mechanisms. The evidence of such risk factors for MINOCA is still scarce and contradicting, as no randomised controlled trials exist in this field. In our work, we performed a review of registries, clinical studies, and case reports of MINOCA, in order to summarise the available data and analyse its possibile pathogenic mechanisms.